An Examination of Islamic Family Law in Kampar Regency, Riau: Focusing on the Causes and Prevalence of Divorce in the Community - Afandi, M. Haikel; Nelli, Jumni; Yunus, Mohd. (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
Marriage is the union of a male and a female to establish a harmonious household, which is a natural inclination of human beings to form partnerships. However, empirical evidence in the field contradicts this notion, since it observes numerous conflicts inside households, sometimes even leading to divorce. Kampa sub-district, located within the Kampar district, recorded a total of 9 divorce cases in the year 2021. The objective of this study is to elucidate the factors contributing to talak divorce in Kampa District and to examine the significance of divorce for those who initiate talak divorce in Kampa District. This study is a sociological investigation that specifically examines the factors contributing to divorce and divorce rates among the residents of Kampa District, Kampar Regency in 2021, with a particular emphasis on the application of Islamic family law. The data collection methods employed were interviews and document analysis. The research findings indicate that the variables contributing to divorce in Kampa District, Kampar Regency include economic circumstances, infidelity, domestic abuse, and educational background. Regarding the significance of divorce for individuals, there are two distinct forms: the notion of liberation and a means of resolving difficulties. In the realm of Islamic family law, divorce is not encouraged, although it is regarded as a viable solution if the household cannot be sustained.